0.18‐μm CMOS wideband passive mixer. Issue 1 (20th November 2012) - Song, Chenyan; Boric‐Lubecke, Olga; Lo, Ivy
Abstract A 0.18‐μm CMOS wideband passive mixer fully integrated with baluns in IBM7HP process is reported. The mixer exhibits wideband operation, despite the intrinsic narrow‐band magnitude balance of passive baluns. Very low DC offset, of less than 3 mV, is achieved without any DC cancellation circuits, due to high LO–RF isolation. At the RF frequency of 2.4 GHz, the combined IF differential outputs provide conversion loss (CL) of 7.5 dB, input 1 dB compression point (IP1dB) of 6.2 dBm, and input third‐order intercept point (IIP3) of 15.5 dBm. This mixer exhibits broad‐band RF impedance matching with reflection coefficient magnitude better than −9.6 dB through the RF frequency range from 1 to 12 GHz. The CL of 10.1–12.9 dB, IP1dB of 8.6–14.4 dBm, and IIP3 of 16–22.2 dBm are achieved at this frequency range for broad‐band applications. © 2012 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:23–27, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/mop.27226